Market Researches which Are Conducted for Introduction of New Product on the Market - Tanasiichuk, Alona; Hromova, Olha; Holovchuk, Yulia; Serednytska, Liudmila; Shevchuk , Anna (European Journal of Sustainable Development, 2020)
At introduction of new product there are many risks which threaten success of goods in the market. To minimize risk, it is necessary to use the correct marketing of a new product, the correct receptions which are capable draw the attention of consumers on just appeared, little-known a product, to make it demanded and it is bought. The main thing, to each business to find the effective strategy of development and advance of a new product. Marketing of a new product differs from traditional market researches. And, first of all, differs in the fact that the assessment of prospects of a new product at stages of its development is carried out in the absence of the market, at total absence of consumers. It creates certain difficulties and increases the probability of mistakes in researches. There are many marketing techniques of advance of new products and services in the modern market. Therefore to businesses and businessmen, for advance of a new product it is necessary to study, first of all, and to effectively use the existing marketing arsenal. Of course, each businessman has to bring the nuances in the experienced methods of marketing. To adapt these receptions for the concrete business, for the marketing of a new product. Keywords: Market researches, new goods, marketing of new goods, technique of promotion of goods, trial marketing, experiment